Evaluating the designed authentic tasks to help students get interested in learning English writing at Thanh Do University - Tran, Thi Kim Nhung (University of Languages and International Studies, 2017)
Authentic tasks are essential in teaching writing since they help students understand and make use of the skill in the real life. Based on the previous researches on authentic learning, some authentic tasks have been designed to help students be more inter (...)